2015
DOI: 10.4081/ijfs.2015.4532
|View full text |Cite
|
Sign up to set email alerts
|

Maiorchino cheese: physicochemical, hygienic and safety characteristics

Abstract: This study assessed the physical, chemical, and microbiological characteristics of traditional Maiorchino cheese (Italy) made from raw ewe’s milk or from a mixture with goat’s milk. Cheese samples from the same batch were analyzed after 20 days and 6, 8, 12, 17 and 24 months of ripening. A decrease in moisture level lead to progressive total solids concentration (fat, total nitrogen, total solids and chloride) during ripening. Aw values decreased from 0.97 (day 20) to 0.85 (month 24), while pH increased from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
5
4
0
1
Order By: Relevance
“…In our study most of the volatile acids found in the ripened cheese were fermentative. In addition the increase in acids found with ripening is in agreement with Conte et al (2015) who reported a lipolytic activity during the maturation period.…”
Section: Volatile Compounds In the Pasture Sheep Milk Yoghurt And Cheesesupporting
confidence: 91%
See 2 more Smart Citations
“…In our study most of the volatile acids found in the ripened cheese were fermentative. In addition the increase in acids found with ripening is in agreement with Conte et al (2015) who reported a lipolytic activity during the maturation period.…”
Section: Volatile Compounds In the Pasture Sheep Milk Yoghurt And Cheesesupporting
confidence: 91%
“…The decrease in alcohol found in the cheeses is due to the ripening, when alcohol binds fatty acids to form esters, as also reported by Conte et al (2015). Seasonal differences in the content of some alcohols have been reported in cheese especially for primary and secondary alcohols (Fernandez-Garcia et al 2004).…”
Section: Volatile Compounds In the Pasture Sheep Milk Yoghurt And Cheesesupporting
confidence: 55%
See 1 more Smart Citation
“…Indeed, Maiorchino (Sample 1, containing sheep milk) was more similar, in terms of Euclidean distance, to cow-derived cheeses (i.e., Ragusano DOP, Sample 5, and Tuma Persa, Sample 6) than other ewe cheeses like Pecorino Siciliano (Sample 2) and Piacentinu Ennese (Sample 3; Figure 6a). These similitudes may trace back to the use of (1) milk mixtures, as Maiorchino is produced using 80% sheep milk and either goat or cow milk, [43] (2) comparable ripening conditions and/or (3) the same rennet for the milk clotting. [44] According to tradition, milk coagulation is mediated by lamb rennet paste for Pecorino Siciliano and Piacentinu Ennese or kid rennet paste for Tuma Persa, although either one of these substances can be used in the case of the other Sicilian cheeses.…”
Section: Chemometric Analyses On Cheese Samplesmentioning
confidence: 99%
“…(Habib el al., 2013;Conte et al, 2015). Berdasarkan persentase berat kering, kadar kalsium tertinggi adalah A1 dengan kadar sebesar 1.511,59±104,27 mg/100g, kemudian diikuti perlakuan A4 (1.446,06±115,46 mg/100g), A2…”
Section: Hasil Dan Pembahasanunclassified